Analisis Perbandingan Trading Volume Activity, Bid-Ask Spread dan Abnormal Return Sebelum dan Sesudah Adanya Pengumuman Stock Split pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode Januari 2015-Oktober 2018 - Anis Zakiyah; Hari Nurweni (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
This study aims to analyze the differences in trading volume activity, bid-ask spread, and abnormal returns before and after the announcement of a stock split in companies listed on the Indonesia Stock Exchange from January 2015 to October 2018. A sample of 39 companies announced a stock split during the period are selected based on certain criteria. The Wilcoxon Signed Rank test is used to analyze the differences in trading volume activity, bid-ask spread, and abnormal returns, five days before and after the announcement. The use of nonparametric statistical analysis was carried out because the data were not normally distributed. The results show that there is no difference in trading volume activity around the announcement of the stock split. On the other hand, the bid-ask spread and abnormal return are statistically different around the announcement of the stock split.